Pengawasan Peredaran Barang Cetakan, Due Process Of Law dan Hak Atas Kebebasan Mengeluarkan Pendapat - Mahrus Ali (The Constitutional Court of the Republic of Indonesia, 2016)
Basically, the authority of attorney general to control the circulations of printed goods is accordance with the principle of due process of law, equality before the law, and the right of freedom of expression as stipulated in the constitution 1945. Interpreting these principles has close relationship with the basic principle of human right in Indonesia, rechtsidee, values, and world view containing in the five basic pillars of Pancasila that stresses more to the balance of right and obligation. In the context of judicial review of an article 30 (3) c act number 16 2004, the problem is not on the existence of its legal norm but on the procedure to implement it in which attorney general did not provide proper and accountable mechanism so that these three principles are not purely conducted.